Development of a topical formulation containing S. Lutea extract: Stability, in vitro studies and cutaneous permeation - Isaac, Vera Lucia Borges [UNESP]; Chiari, Bruna G. [UNESP]; Miglioli, Kamila [UNESP]; Moreira, Raquel [UNESP]; Oliveira, José Ricardo Soares; Salgado, Hérida [UNESP]; Relkin, Perla; Correa, Marcos Antonio [UNESP]; Salgado, Ana; Ribeiro, Helena M. (SAGE Publications, 2012)
Flavonoids have been widely incorporated into cosmetic and dermatological formulations, affording benefits such as antioxidant action, improved skin tone and fewer lines and wrinkles. Brazil has a huge biodiversity, with one of the richest flora in the world, and existing studies justify the quest for greater research efforts in this area. The cajazeira (Spondias lutea L.), a plant of the Anacardiaceae family from tropical America, is widely disseminated in Brazil. This plant was chosen because of the presence of flavonoids that exhibit antioxidant activity. The purpose of this research was to develop a stable topical formulation containing Spondias lutea extract with the aim of preventing skin diseases caused by UV radiation. Hydro ethanolic extract of Spondias lutea fruit was prepared and assayed for its the flavonoids content. The antioxidant activity was estimated by DPPH and superoxide assay. The physicochemical stability and skin permeation of the cream containing 8% (w/w) of extract were assessed. The results showed that the S. lutea extract possessed antioxidant activity, and that it is possible to obtain a stable cosmetic containing the extract, which is able to penetrate the skin. Thus, it is possible to use this extract to produce an anti-aging cosmetic.
Keywords: Antioxidant; Cutaneous permeation; Emulsion; Quercetin; Rutin; Spondias lutea